2022
DOI: 10.3390/jpm12060920
|View full text |Cite
|
Sign up to set email alerts
|

Integrated microRNA–mRNA Expression Profiling Identifies Novel Targets and Networks Associated with Autism

Abstract: Autism spectrum disorder (ASD) is a complex neurodevelopmental disorder, with mutations in hundreds of genes contributing to its risk. Herein, we studied lymphoblastoid cell lines (LCLs) from children diagnosed with autistic disorder (n = 10) and controls (n = 7) using RNA and miRNA sequencing profiles. The sequencing analysis identified 1700 genes and 102 miRNAs differentially expressed between the ASD and control LCLs (p ≤ 0.05). The top upregulated genes were GABRA4, AUTS2, and IL27, and the top upregulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…miRNA was measured in lymphoblastoid cell lines in three studies [14,22,29], five studies measured miRNA in postmortem cerebral cortex tissues [2,15,[30][31][32], one study used cells from the olfactory mucosa [18], thirteen studies used serum [7,19,24,[33][34][35][36][37][38][39][40][41][42], and five studies used saliva [8,16,[43][44][45]. A recent narrative review [46] found that the miR-151a, miR-146a, and miR-27a-30 are dysregulated in people with ASD and are replicated in more than one tissue.…”
Section: Resultsmentioning
confidence: 99%
“…miRNA was measured in lymphoblastoid cell lines in three studies [14,22,29], five studies measured miRNA in postmortem cerebral cortex tissues [2,15,[30][31][32], one study used cells from the olfactory mucosa [18], thirteen studies used serum [7,19,24,[33][34][35][36][37][38][39][40][41][42], and five studies used saliva [8,16,[43][44][45]. A recent narrative review [46] found that the miR-151a, miR-146a, and miR-27a-30 are dysregulated in people with ASD and are replicated in more than one tissue.…”
Section: Resultsmentioning
confidence: 99%
“…The expression of hsa-miR-6813-3p and hsa-miR-2277-3p was significantly lower in the MD group than in the healthy control group. Previous work has reported that miR-6813-3p is involved in ASD [ 44 ]. Prior research has also shown that miR-2277-3p is involved in colon cancer cells [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Li et al reported that miR-199a-3p is dysregulated in neurons of children with epilepsy, which is regulated by lncRNA-TUBG1 and associated with neuron apoptosis and biological behaviors ( 50 ). Moreover, miR-21-5p has been implicated in a variety of neurological disease, i.e., epilepsy, dementia, Alzheimer's disease, and autism, along with regulating apoptosis of hippocampal neurons ( 17 , 51 53 ). It has been suggested by the findings that these four miRNAs may be crucially involved in epileptogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Research by Johnson et al suggested that the reduced expression of miR-1307-3p in the saliva of children who experienced concussion predicted a significantly high probability of conversion to (50). Moreover, miR-21-5p has been implicated in a variety of neurological disease, i.e., epilepsy, dementia, Alzheimer's disease, and autism, along with regulating apoptosis of hippocampal neurons (17,(51)(52)(53). It has been suggested by the findings that these four miRNAs may be crucially involved in epileptogenesis.…”
Section: Discussionmentioning
confidence: 99%